Foucauldian contributions on racism: parallels between Indigenous soldiers from the United States and Brazil - Moreira, Nádia Xavier; Caminha, Viviane Machado (Argumentum, 2025)
This paper reflects, from a Foucauldian perspective on racism, on the participation of Indigenous individuals as military professionals in the Armed Forces of the United States and Brazil. It is a qualitative study based on bibliographic and documentary analysis, complemented by data collection from websites (e.g. YouTube) and institutional videos using the key term Indigenous soldiers. The primary finding is the presence of biological racism, either through the stereotypical expectation of Indigenous individuals as natural warriors or through the simplistic perception of their contribution as mere exchange of knowledge. These practices reinforce class distinctions, characterised by differences in rank and compensation received for their service.